Functional PIN1 promoter polymorphisms associated with risk of nasopharyngeal carcinoma in Southern Chinese populations - Liuyan Zeng (Nature Portfolio, 2017)
Abstract Our previous work reported the association between two single nucleotide polymorphisms (SNPs) in PIN1 promoter and nasopharyngeal carcinoma (NPC) risk with a small sample size in a low incidence area. This study investigated the association between the two SNPs and NPC risk in 733 patients and 895 controls from a high incidence area. The results indicated the genotype and allele frequencies of -842G > C and -667C > T were both significantly different between patients and controls even using the resampling statistics. The -842GC and -667TT genotypes showed a significantly increased risk of NPC (OR = 1.977, 95% CI = 1.339–2.919, P = 0.001 and OR = 1.438, 95% CI = 1.061–1.922, P = 0.019, respectively). Compared to the most common -842G-667C haplotype, -842G-667T haplotype and -842C-667C haplotype showed a significantly increased risk of NPC (OR = 1.215, 95% CI = 1.053–1.402, P = 0.008 and OR = 2.268, 95% CI = 1.530–3.362, P = 0.001, respectively). Further reporter gene expression suggested that variant -842C-667C and -842G-667T were associated with an enhanced transcriptional activity. In conclusion, our findings suggest that -842G > C and -667C > T in PIN1 promoter are associated with NPC risk; as well as the promoter activity is mediated by functional PIN1 variants.